Perceptions of Oral Health Technicians for the practice of preventive actions against dental caries (Research, Society and Development, 2022)
The objective of this study was to identify strategies for the prevention of dental caries in oral health teams. A focus group was carried out with Oral Health Technicians working in the Basic Health Units of the municipalities of the 15th Regional Health Department of the Paraná State Health Department, based on a semi-structured script, a moderator and an annotator, with the meeting being recorded and filmed. The transcription of the recording was performed manually and the speeches were analyzed according to the content analysis method proposed by Bardin, using the Atlas ti 8.0 software. Three facilitating strategies for the prevention of dental caries were identified: “Implementation of Preventive Procedures”, “Permanent Health Education” and “Empathy and Patient Motivation”. The Oral Health Technicians pointed out viable strategies for the practice of dental caries prevention, which can contribute to the improvement of the population's health care.